High edge-nitrogen-doped porous carbon nanosheets with rapid pseudocapacitive mechanism for boosted potassium-ion storage. (February 2022) - Zhu, Lingfeng; Wang, Yun; Wang, Minji; Huang, Mouzhi; Huang, Yanan; Zhang, Ze; Yu, Ji; Qu, Yaohui; Li, Chao; Yang, Zhenyu
Abstract: Currently, the development of carbonaceous materials for potassium ion batteries (PIBs) with ultrafast rate performance is limited by the huge volume expansion and sluggish electrochemical kinetics derived from the insertion/de-insertion of large radius of K + . Herein, the high edge-nitrogen-doped porous carbon nanosheets (EN-PCNs) were obtained via a simple and scalable pyrolysis strategy. The synergistic effect of two-dimensional (2D) porous nanosheet structure and ultrahigh content of edge-nitrogen (79.6 at%) provide the EN-PCNs with multiple advantages including rich defect sites, enlarge interlayer spacing (0.378 nm) and high specific surface area (417.0 m 2  g −1 ), which can enhance the K + storage. As excepted, the as-prepared EN-PCNs electrode delivers a high reversible capacity of 345.2 mA h g −1 at 0.7 C, ultrafast rate capacity of 108.4 mA h g −1 at 7 C and good cycling stability of 121.4 mA h g −1 with a retention of 72% after 1000 cycles at 3.5 C. Moreover, in-depth electrochemical kinetic analysis further verifies that the boosted potassium ion storage of EN-PCNs electrode is attributed to the rapid pseudocapacitance mechanism. This work not only demonstrates a simple and scalable strategy for the construction of advanced high edge N-doped porous nanosheet carbon materials, but also provides a new reference for adjusting the pseudocapacitance mechanism to achieve enhanced potassium storage capacity. Graphical abstract: The high edge-nitrogen-doped porous carbon nanosheets (EN-PCNs) were prepared via a simple and scalable pyrolysis strategy and exhibited boosted potassium ion storage including the high reversible capacity, ultrafast rate performance along with excellent cycling stability. Image 1 Highlights: The EN-PCNs were synthesized via a simple and scalable pyrolysis strategy. High nitrogen doping level (5.7 at%) and unique 2D porous nanosheet structure. High reversible capacity, ultrafast rate performance and good cycling stability of EN-PCNs electrode. In-depth electrochemical kinetic analysis verifies the rapid pseudocapacitance mechanism of EN-PCNs electrode.